Cold-stimulated brown adipose tissue activation is related to changes in serum metabolites relevant to NAD+ metabolism in humans - U-Din Mueez; de Mello Vanessa D; Tuomainen Marjo; Raiko Juho; Niemi Tarja; Fromme Tobias; Klåvus Anton; Gautier Nadine; Haimilahti Kimmo; Lehtonen Marko; Kristiansen Karsten; Newman John W; et al. (Cell Press, 2025)
Cold-induced brown adipose tissue (BAT) activation is considered to improve metabolic health. In murine BAT, cold increases the fundamental molecule for mitochondrial function, nicotinamide adenine dinucleotide (NAD+), but limited knowledge of NAD+ metabolism during cold in human BAT metabolism exists. We show that cold increases the serum metabolites of the NAD+ salvage pathway (nicotinamide and 1-methylnicotinamide) in humans. Additionally, individuals with cold-stimulated BAT activation have decreased levels of metabolites from the de novo NAD+ biosynthesis pathway (tryptophan, kynurenine). Serum nicotinamide correlates positively with cold-stimulated BAT activation, whereas tryptophan and kynurenine correlate negatively. Furthermore, the expression of genes involved in NAD+ biosynthesis in BAT is related to markers of metabolic health. Our data indicate that cold increases serum tryptophan conversion to nicotinamide to be further utilized by BAT. We conclude that NAD+ metabolism is activated upon cold in humans and is probably regulated in a coordinated fashion by several tissues.